CASE SERIES OF OSTEOMALACIA SECONDARY TO RENAL TUBULAR ACIDOSIS TYPE 1 WITH VITAMIN D DEFICIENCY - Jeevaraj, Lavanya; Sambamoorthy, Vijayrama Rao; Nordin, Hidayatil Alimi Bin Keya; Rahim, Anilah Bt Abdul; Rahmatullah , jaz Bt Hallaj (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Osteomalacia is a disease of inadequate bone mineralization.Its association with RTA type 1 is less established. Early recognition is essential to treat and prevent osteomalacia. We report 2 cases of Malaysian females with osteomalacia and RTA type 1. The first patient, 36 years old, was wheelchair-bound. Initial BMD showed a hip Z-score of -3.9 and a T-score of -4.0. Recent BMD showed a hip Z-score of -1.5 and a T-score of -1.6. The second patient, 38 years old, presented with muscle weakness and bone pain. The vitamin D level was 9.6 nmol/L. Initial BMD showed a T-score of -2.1. The latest BMD showed a T-score of 1.7 and a Z-score of 1.7. Both patients made a complete recovery after initiation of treatment. Type 1 RTA may present later with osteomalacia. Correction of acidosis along with the concomitant correction of vitamin D is crucial to successfully treat these patients.